Long-term outcome after catheter ablation of paroxysmal atrial fibrillation: Impact of different atrial fibrillation foci. (15th January 2017) - Takigawa, Masateru; Takahashi, Atsushi; Kuwahara, Taishi; Okubo, Kenji; Takahashi, Yoshihide; Watari, Yuji; Nakashima, Emiko; Nakajima, Jun; Yamao, Kazuya; Takagi, Katsumasa; Tanaka, Yasuaki; Fujino, Tadashi; et al.
Abstract: Background: We aimed to determine whether differing foci in paroxysmal atrial fibrillation (PAF) affected the long-term outcome of catheter ablation (CA). Methods: A total of 865 consecutive PAF patients (age, 61 ± 10 years; 670 male) undergoing initial AF ablation were included. After pulmonary vein (PV) isolation, superior vena cava (SVC) isolation was performed for SVC foci; other non-PV foci were focally ablated. Long-term outcomes were compared among patients with SVC foci (Group SVC), other non-PV foci (Group Non-PV), and those without these foci (Group PV). Results: Groups PV, SVC, and Non-PV contained 740 (85.8%), 57 (6.6%), and 68 (7.6%) patients, respectively. Structural heart disease (P = 0.01) and duration of AF history (P = 0.04) were significantly associated with Group Non-PV, and female sex (P = 0.0002) was significantly associated with Group SVC. AF recurrence-free rates at 5 years in Group PV, SVC, and Non-PV were 62.0%, 66.3%, and 49.3%, respectively (P = 0.03), after the initial CA, and 84.7%, 83.9%, and 77.0%, respectively (P = 0.02), after the final CA. The duration of AF history (HR, 1.04, P < 0.0001) and left atrial dimension (HR, 1.37 per 10 mm increase, P = 0.0003) were significant predictors of AF recurrence after the initial CA. Although Group Non-PV was weakly associated (HR 1.38, P = 0.08) with AF recurrence, Group SVC was not associated with AF recurrence. Conclusions: Long-term outcome of CA of PAF was significantly worse in patients with non-PV foci other than SVC foci. These foci may affect the outcome not independently but as an aspect of atrial remodeling.